Psychological features of aggressiveness of smoking female students - I A Novikova; A L Novikov (Peoples' Friendship University of Russia (RUDN University), 2014)
The paper presents the results of a comparative study of the aggressiveness level in smoking and nonsmoking female students. The System-Functional Model of Aggressiveness developed by A.I. Krupnov has been used in the study. The results confirm the hypothesis that smoking female students in general have a higher level of aggressiveness in comparison with the non-smokers, although the level of aggressiveness in both groups did not exceed the norm.